A relict habitat became an isolated habitat in the Luoshan Nature Reserve from 1977 to 2017: Natural or man‐made disaster?. (28th October 2019) - Ma, Chao; Wang, Xiabing; Zhang, Wenhao
Abstract : Understanding the ecological trends of the relict habitats in the Luoshan Nature Reserve (LNR) has an important role in the persistence of endangered species and the socio‐economic sustainability in the Ningxia section of the arid desertification belt in North China. Based on data from the Landsat Multispectral Scanner (MSS)/Thematic Mapper (TM)/Enhanced Thematic Mapper Plus (ETM+)/Operational Land Imager (OLI) sensors (from 1977 to 2017), the MODIS normalized difference vegetation index (NDVI) and net primary productivity (NPP) (from 2000 to 2017), the Shuttle Radar Topography Mission (SRTM) digital elevation model (DEM), annual average air temperature and precipitation (from 1977 to 2017), typical anthropogenic factors (population size, cultivated land and residential area) and natural ecological elements (MSS/TM/ETM+/OLI/MODIS NDVI and NPP) were quantitatively contrasted and analyzed for potential correlations. Some indicators of human activities, ecological processes and landscape geography have changed in the LNR. The proportion of residential area increased 3.09‐fold from 1977 to 2017. The population increased 34.30‐fold due to ecological immigration policy implementation in the Hongsipu immigration district. Before immigration, cultivated land increased, but after immigration, this land decreased quickly. Most of the dry‐cultivated land was converted through afforestation and a small part of the land was converted to irrigate cultivation land. We conclude that natural evolution led to the ecological relics, the isolated management to the LNR has objectively created an ecological island that will accelerate inbreeding depression and reduce biodiversity.